A macro-map of medical technologies: introductory thoughts. (1st January 2000) - van Wyk, Rias J
This article suggests an approach to creating a macro-map of medical technologies. Such a map is needed to help medical professionals and technology producers explore possible future developments in medical technology. The approach suggests the use of five frameworks constituting the fundamental structures of strategic technology analysis. Two of these frameworks are tested on a sample of seven medical technologies. The effort seems justified. There is a gain in structure and simplicity. It is proposed that the approach be further extended using all five fundamental frameworks and a larger sample of medical technologies.